Artificial Intelligence and Industrial Applications Algorithms, Techniques, and Engineering Applications - Masrour, Tawfik; Ramchoun, Hassan; Hajji, Tarik; Hosni, Mohamed (Lecture Notes in Networks and Systems, 2023)
XXII, 472 p. 261 illus., 197 illus. in color.